Pengaruh Kepribadian Proaktif, Efikasi Diri dan Anticipatory Entrepreneurial Cognitions dalam Membentuk Niat Berwirausaha Mahasiswa - Meisa Amanda; Suryandari Istiqomah; Sarjiyanto Sarjiyanto (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2020)
This research aims to examine how a proactive personality and entrepreneurial self-efficacy of students may affect the entrepreneurial intentions in students is mediated by the creative self-efficacy, learning self-efficacy and anticipatory entrepreneurial cognitions. This research was conducted on students of Sebelas Maret University, taken using the technique of probability sampling that is stratified random sampling with the number of respondents in this study as much as 610 students. This research uses the structural equation modeling. The results of this research it can be concluded that: 1) proactive personality of Sebelas Maret University’s students associated positively with entrepreneurial self-efficacy that is mediated by creative self-efficacy and learning self-efficacy; 2) trait competitiveness of Sebelas Maret University’s students associated positively with entrepreneurial self-efficacy that is mediated by the creative self-efficacy and learning self-efficacy; 3) entrepreneurial self-efficacy of Sebelas Maret University’s students were associated positively with students entrepreneurial intentions is mediated by anticipatory entrepreneurial cognitions. This research has limitations in terms of subject and object of research, because the focus of the research only to students who are still active in the college’s activities and conducted in Sebelas Maret University’s environment. So in the next research is expected to complete the limitations in this research.